11x+2 = 9x+6. Subtract 2 from both sides. 11x = 9x+6. subtract 9x from both sides. 2x = 4, divide both sides by 2. x = 2. Substitute the x with 2 and check to see it it works. The numbers should equal each other.
5x^3+8x^2/3x^4-16x^2=x^2(5x+8)/x^2(3x^2-16)=5x+8/3x^2-16
lim x--->0 5x+8/3x^2-16=8/-16=-1/2
Answer:
A, B, E
Step-by-step explanation:
I attached everything that I thought it would help you.
Hope this helps ;) ❤❤❤
Answer:
x^2-16
Step-by-step explanation:
A= (b)(h)
A= (x+4)(x-4)
x^2-4^2
x^2-16
Y = 2x/x-7
x = 2y/y-7
xy - 7x = 2y
-7x = 2y - xy
-7x = y(2-x)
y = -7x / 2-x
y = 7x / x-2
f-¹(x) = 7x / x-2